(3HGH aj GdMSGHs
(3ChdgG (B:s
(3HGH ai GdMSGH GYde Cf ddMSGH CQHY efGRd BMGO hYTQGJ heFGJ hCdha s
(3BNQgG (B:s
(3aGdNGQL ef bSeI GdKdGKI hGdKdK Ydi GdNeSI KdKGf hYdi gPG jbGS fXGFQg s
(3GdfSNI HgG MhGTs
(3YdjgG bQGAI SfI (B773(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(2 / 7189) s
Keywords: (3GdQjGVjGJs